Backward and forward Monte Carlo method for vector radiative transfer in a two-dimensional graded index medium. (October 2017) - Qian, Lin-Feng; Shi, Guo-Dong; Huang, Yong; Xing, Yu-Ming
Abstract : This paper studied the vector radiative transfer in 2D graded index medium. We developed a backward and forward Monte Carlo method. The Runge–Kutta ray tracing method is used. Abstract: In vector radiative transfer, backward ray tracing is seldom used. We present a backward and forward Monte Carlo method to simulate vector radiative transfer in a two-dimensional graded index medium, which is new and different from the conventional Monte Carlo method. The backward and forward Monte Carlo method involves dividing the ray tracing into two processes backward tracing and forward tracing. In multidimensional graded index media, the trajectory of a ray is usually a three-dimensional curve. During the transport of a polarization ellipse, the curved ray trajectory will induce geometrical effects and cause Stokes parameters to continuously change. The solution processes for a non-scattering medium and an anisotropic scattering medium are analysed. We also analyse some parameters that influence the Stokes vector in two-dimensional graded index media. The research shows that the Q component of the Stokes vector cannot be ignored. However, the U and V components of the Stokes vector are very small.